The effect of a healthy nutritional program on body mass index and anthropometric measurements in obese women - Tuaimah, Mohammed Hasan; Kuswoyo, Dilli Dwi (Universitas Tanjungpura, 2025)
Background. Overweight and obesity represent significant health challenges in contemporary society, particularly during periods of stunted physical development and hormonal imbalance. These conditions increase the risk of serious health issues, including coronary heart disease and high blood pressure. Addressing these problems through non-invasive and sustainable approaches is crucial, particularly among women. Objectives. This study aims to design a physical nutrition program incorporating circuit training to promote weight loss in women. Specifically, it seeks to determine the program